Influence of Ba Doping on the Electrical Behaviour of La0.9Sr0.1Al0.9Mg0.1O3−δ System for a Solid Electrolyte - Verma O.N.; Singh S.; Singh V.K.; Najim M.; Pandey R.; Singh P. (My University, 2025)
Barium (Ba)-incorporated strontium and magnesium-doped lanthanum aluminate, La0.9−xSr0.1BaxAl0.9Mg0.1O3−δ (LSBAM, with x = 0.00, 0.01 and 0.03) designated as LSBAM 00, LSBAM 01 and LSBAM 03, respectively, were effectively synthesized via citrate–nitrate-based auto-combustion method taking citric acid (C6H8O7·H2O) as a fuel agent. The electrical properties of the synthesized compositions were investigated as electrolyte for electrochemical applications. The powders were also characterized by simultaneous differential thermal analysis and thermogravimetric analysis to confirm the reaction temperature of the final product from the precursor. The X-ray Rietveld refinement patterns showed the rhombohedral structure with space group R-3c of the investigated systems. The scanning electron microscope images depicted fairly dense micrographs that are essential for a good electrolyte. The crystallite sizes were estimated to be in the range of 40 nm to 55 nm. The effect of doping has been investigated for the further improvement of ionic conducting efficiency of the systems. The electrical conductivity of the La0.9−xSr0.1BaxAl0.9Mg0.1O3−δ system has been measured at different temperatures between 400°C and 700°C to reveal the contribution of grains, grain boundaries and electrode specimen interface response to the total conductivity. The values of activation energy (Ea) for total conductivity suggest ionic conduction in the system that may primarily be due to the diffusion of O2− ions via oxygen vacancy sites. The conductivity for all compositions was found to increase with increasing temperature. © 2021, The Minerals, Metals & Materials Society.